Water and conflicts around religious heritage: oscillations between centre and periphery? - Lazzaretti, Vera (Split waters, 2021)
This chapter discusses the case of the Well of Knowledge in Banaras (Uttar Pradesh, India), whose water is depicted by Hindu textual traditions and oral narratives as a source of wisdom and ultimately liberation from rebirth. The Well is located at the heart of the city’s religious life, in the highly sensitive Vishvanath temple and Gyan Vapi mosque compound. The chapter illustrates the ‘oscillating’ role of water in the process of heritage making at this site. In exploring the development of a mainstream narrative that depicts the compound as a site of Hindu-Muslim conflicts, I first point to the centrality of the Well to this narrative, particularly during colonial times. From the 1980s onwards, however, national concerns for security and the priority assigned to urban development relegated the Well with its symbolic capital to a peripheral role. These concerns, I then argue, have also obscured the subtler disputes—staged around the Well—which unfold instead within the Hindu domain and therefore challenge unitary representations of Hinduness and heritage advocated by Hindu nationalist forces. Recent attempts to implement a controversial development plan have now revealed these inner disputes, and the Well itself, I suggest, might soon regain centrality.